SCHOOL ADMINSTRATOR’S DECISION MAKING AND CURICULUM IN SCHOOL UNDER KANCHANABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Akkaraphichart, Siraprapa; Rattanasiraprapha, Nuchnara (Journal of Educational Review Faculty of Education in MCU, 2025)
This research was purposed to know 1) Decision of school administrators under the Kanchanaburi primary educational service office 1 2) Curriculum management in school under the Kanchanaburi primary educational service office 1 and 3) Relation between Decision of school administrators under the Kanchanaburi primary educational service area office 1. The samplings of this research were educational institution of educational institution under the Kanchanaburi primary educational service office 1 103 samplings, key performances were 2 per each educational institution consists of 1 of educational administrator and 1 teacher total 206. The research tool is questionnaire about decision making of educational administrators of Gordon, and curriculum administration follow by academic office and educational standards, the statistic are frequency, percentage, arithmetic middle, standard deviation and Pearson's correlation coefficient. The result found that 1) Decision making of administrators of educational institution under the Kanchanaburi primary educational service office 1 overall and each aspect is at a high level arrange the arithmetic mean values from highest to lowest as follows searching for alternatives, situation analysis, decision evaluation, decision, setting objectives, and evaluating alternatives. 2) Curriculum administration of educational institution under the Kanchanaburi primary educational service office 1 overall and each aspect is at a high level arrange the arithmetic mean values from highest to lowest as follows planning for implementing the school curriculum, preparation of school curriculum, conclusion, operations and report writing, supervision, monitoring and evaluation, improving and developing the curriculum management process, implementation of curriculum management and preparation of educational institutions. 3) Decision making of administrators of educational institution under the Kanchanaburi primary educational service office 1 statistical significance as 0.01 at high level and correlation coefficient (rxy = 0.871)